2021
DOI: 10.20961/jmpf.v11i1.47358
|View full text |Cite
|
Sign up to set email alerts
|

Eksperimen Model Discovery Learning dan Problem Based Learning Didukung Modul LCDS Ditinjau dari Ketekunan Belajar Siswa SMA Materi Hukum Newton tentang Gerak

Abstract: Tujuan penelitian yaitu mengetahui ada atau tidak : 1) perbedaan pengaruh model discovery learning dan problem based learning didukung modul LCDS terhadap hasil belajar kognitif, 2) perbedaan pengaruh antara tingkat ketekunan belajar terhadap hasil belajar kognitif, dan 3) interaksi antara pengaruh model pembelajaran dan tingkat ketekunan belajar fisika terhadap hasil belajar kognitif. Metode penelitian ini yaitu eksperimentasi dengan desain faktorial 2x2. Populasi penelitian ialah seluruh peserta didik kelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Student learning perseverance is included in a scientific attitude as an investigative effort or action to solve a problem or problem (Amin et al, 2021;Fang et al, 2017;Ilma et al, 2021). Perseverance in independent learning has a strong impact on the level of achievement achieved by students, by increasing the relationship between motivation and the learning process of students (Amin et al, 2022;Kırbas, 2018;Tamardiyah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Student learning perseverance is included in a scientific attitude as an investigative effort or action to solve a problem or problem (Amin et al, 2021;Fang et al, 2017;Ilma et al, 2021). Perseverance in independent learning has a strong impact on the level of achievement achieved by students, by increasing the relationship between motivation and the learning process of students (Amin et al, 2022;Kırbas, 2018;Tamardiyah, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature on the subject revealed that it was seen that many experimental researches (Deveci, 2002;Arıcı, 2021;Çanakçı, 2021;Dita et al, 2021;Foo et al, 2021;Ghani et al, 2021;Hasanah et al, 2021;Lestari et al, 2021;Ilma et al, 2021;Putri and Sundayana, 2021;Sari et al, 2021;Shofwani and Rochmah, 2021;Simanjuntak et al, 2021;Suparman et al, 2021;Fong et al, 2022;Kim et al, 2022;Putri et al, 2022;Safitri et al, 2022;Tanrıkulu, 2022;Trullas et al, 2022) were conducted on PBL. It was determined that the researches in the literature focused on determining the effectiveness of PBL in different subjects and comparing it with various learning approaches.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Aswita et al, 2022), exploring ideas has several aspects: perseverance, thoroughness, creativity, and conceptual reasoning. Perseverance is one of the factors for student learning success through acceptance of experience, which is characterized by a scientific attitude in conducting investigations, discipline, and tenacity (Ilma et al, 2021;Miarsyah et al, 2019;Tamardiyah, 2017). Thorough is a habit of doing something according to the appropriate steps and cannot be wrong (Ja'far, 2014).…”
Section: Introductionmentioning
confidence: 99%